1986
DOI: 10.1139/b86-379
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal pattern of biomass allocation in flowering and nonflowering specimens of three Pinguicula species

Abstract: KARLSSON, P. S. 1986. Seasonal pattern of biomass allocation in flowering and nonflowering specimens of three Pinguicula species. Can. J. Bot. 64: 2872 -2877. The seasonal patterns of biomass allocation in flowering and nonflowering specimens of Pinguicula alpina L., P. villosa L., and P. vulgaris L. were compared in a subarctic environment. Pinguicula alpina had a large perennial root system, comprising 50% of the nonreproductive biomass. The other two species had smaller, annual roots, representing 5 -10% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 10 publications
2
45
0
Order By: Relevance
“…Most of ovules develop into seeds (pers. observation), and the number of seeds per fruit is similar or higher than in its European congeners (P. alpina, P. villosa and P. vulgaris) (Karlsson, 1986). These results, together with the particular strategy of seeds dispersal and the easiness of vegetative propagation, suggest that P. longifolia reproduces without problems, and that it is a plant well adapted to the habitat where it lives.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Most of ovules develop into seeds (pers. observation), and the number of seeds per fruit is similar or higher than in its European congeners (P. alpina, P. villosa and P. vulgaris) (Karlsson, 1986). These results, together with the particular strategy of seeds dispersal and the easiness of vegetative propagation, suggest that P. longifolia reproduces without problems, and that it is a plant well adapted to the habitat where it lives.…”
Section: Discussionmentioning
confidence: 59%
“…Several studies have focused on the cytology, physiology and feeding ecology of Pinguicula (Heslop-Harrison and Knox, 1971 ;Karlsson and Carlsson, 1984 ;Karlsson, 1986 ;Karlsson et al, 1987Karlsson et al, , 1990Zamora, 1990 ;Antor and Garcia, 1994); however, there are very few references on their biology and reproduction in natural conditions (see Molau, 1993). The aim of this study is to provide information about some of these aspects (life cycle, breeding system, pollinators, reproductive succss ... )…”
Section: Resume-on a Etudie Le Cycle De Vie Et Ia Biologie De Ia Repmentioning
confidence: 99%
“…It has been suggested that due to the continuous upward movement of Sphagnum, the co-occurring vascular plants need to allocate resources to vertical growth to keep pace with the Sphagnum carpet (Backeus 1985, Thum 1988, Karlsson 1986, Svensson et al 1993, Malmer et al 1994. The present results support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Within a species, SRE values were shown to vary markedly within and among populations (e.g., Douglas 198 1;Ashmun et al 1985;Karlsson 1986;Hartnett 1990) and between years (Ohlson 1988). However, much of the variation in SRE can be accounted for by size-dependent reproductive allocation, rather than external effects (Samson and Werk 1986;Weiner 1988).…”
Section: Introductionmentioning
confidence: 99%